Paradoxical Antidepressant Effects of Sleep Deprivation in Depression: Mechanisms, Clinical Effects, and Therapeutic Implications - Arkadiusz Jaworski; Michał Szyszka; Karolina Brzostek; Jakub Sobieraj; Wiktoria Lewicka; Weronika Misiąg-Marmura; Konrad Szaliński; Pola Soczomska; Małgorzata Stopa; Izabella Sośniak (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Sleep deprivation (SD), paradoxically, has been shown to induce rapid antidepressant effects in patients with depressive disorders. This review explores the neurobiological underpinnings, clinical efficacy, and therapeutic strategies involving SD, aiming to clarify the mechanisms responsible for its mood-elevating effects and to assess its role in modern treatment of depression.